PENYELESAIAN UTANG PERSEROAN TERBATAS YANG DINYATAKAN PAILIT YANG OBJEK JAMINANNYA MILIK PIHAK KETIGA - MAHYANI MAHYANI (PREMISE LAW JURNAL, 2014)
ABSTRACT Insolvent debtors debt settlement guarantee that the object belongs to a third party under debts caused its own problems, especially if the debtor is a legal entity in the form of a limited liability company (PT), because the PT has a position independent and have separate responsibilities of the organs of the company. The use of collateral objects belonging to the company organs raises PT overlapping responsibilities with each organ of the company. The process of debt settlement to bankruptcy if the debtor objects belonging to a third party guarantee is essentially the same as debt settlement bankruptcy debtors. The constraints in the debt settlement bankruptcy debtor objects guarantee that third party, is the resistance of any appeal rights grantor guarantees to the above objections forced letter, the land has been leased before the collateral, the collateral is the property gono-gini, or an auction price is too low, difficult to find buyers and enthusiasts auction buyers auction bit. Keywords : Paying off Debt, Collateral Owned by the Third Party